Inventory Of Atmospheric Emission In Malaysia Computation Of Data And Estimation For combustion In Industry. - Abd Hamid, Mohd Azizi (2004)
Emission inventorv is usually used for air quality modeling and air quality planning requires appropriate spatial and temporal resolution.